Climate Literacy and Individual Consumption Behavior: An Evaluation of the Indian Experience - P. Singh, Kanwal D.; Mathur, Aakriti (European Journal of Sustainable Development, 2019)
Climate change education and awareness are essential for any effective action on climate change. While regulatory policies and taxes influence consumer behavior, these measures are significantly more successful when the stakeholders are made aware of the larger policy objective underlying such measures, especially the exact extent and nature of the impact of climate change, if Greenhouse Gas (GHG) emissions continue unabated as also the significant effect small everyday individual choices can have on reducing the individual GHG emissions. This paper will examine the extent of awareness regarding the causes and consequences of climate change as also the government programs and policies for climate change mitigation and adaptation. It will also evaluate the effect of climate literacy on individual consumption habits and attitudes towards climate change mitigation and adaptation. The methodology adopted in this research paper will be empirical and analytical and the authors will collect primary data through the means of a questionnaire administered to a random sample of 300 respondents belonging to the age group of 18 – 75 years, selected from urban areas in India. The research paper shall show the relationship between lack of climate literacy and high GHG emissions through individual consumption habits and behavior and make recommendations for increasing climate literacy in India through effective outreach programs. Keywords: Climate Literacy, Individual Carbon Emissions, Consumption Behavior, Attitudes to Climate Change